Modal coupling in surface-corrugated long-period-grating fiber tapers. - Ding,W; Andrews,SR; Maier,SA (Opt Lett, 2008)
We describe the properties of a surface-corrugated long-period-grating fiber taper fabricated using contact optical lithography and wet etching techniques. The preservation of cylindrical symmetry in this device facilitates investigation of the modal behavior. Comparison of the measured and calculated transmission spectra reveals that the widely used coupled-mode theory is not applicable. Instead, a mode-projection model, in which modal propagation and coupling are treated separately within the grating, explains the experiments very well.